Pengaruh kepimpinan beretika, kefahaman integriti dan nilai profesional terhadap amalan etika akademik pensyarah perguruan tinggi keagamaan Islam negeri (PTKIN) di Aceh, Indonesia - , Sufriadi (2019)
The phenomenon of deteriorating academic ethics practices among lecturers is alarming in Indonesia. This can be seen in the depreciation of ethics values, integrity and professionalism value among lecturers. Therefore, this study focuses on the influence of ethical leadership, integrity understanding and professional values on lecturer's academic ethics practice. The methodology of this study used quantitative method through survey. The data of this study were collected using questionnaire whereby ethical leadership was measured by using the Ethical Leadership at Work (ELW) from Kalshoven, Den Hartog & De Hoogh (2011), integrity understanding was measured using questionnaires by Hanafi Hamdani (2014), professional values were measured using questionnaires by Wilson (2010) and academic ethics practices were measured using the College Teaching Behaviors Inventory (CTBI) built by Braxton & Bayer (2003). Disproportional stratified random sampling method was used. 439 lecturers were randomly selected from five Islamic State Higher Education Institutions (PTKIN) in Aceh, Indonesia. The findings show that there is no significant relationship between ethical leadership (r=.090; .058) with lecturer's academic ethics practice. Whereas, the findings show that there is a significant positive relationship between integrity understanding (r=.113; .017) and professional value (r=.105; .028) with academic ethics practices of lecturers. The findings also show that there is no significant influence between ethical leadership (β=.051; .321), integrity understanding (β=.083; .102) and professional value (β=.056; .297) towards lecturer's academic ethics practice. In addition, the findings also show that integrity comprehension greatly contributes to the changes in academic ethics practices of PTKIN lecturers compared to ethical leadership and professional values. The implications of this study indicate that the aspect of ethical leadership, integrity understanding and professional values are enhanced through courses and training organized by top management of PTKIN.